Cessation of Smoking and Alcohol Addiction Following Thalamic Hemorrhage. Issue 6 (November 2016) - Najeeb, Fatima; Silver, Brian; Khan, Muhib
Abstract : Introduction: We describe a case of thalamic intracerebral hemorrhage leading to cessation of smoking. Case Report: A 53-year-old female presented to the emergency department with right-sided weakness and dysarthria. Initial systolic blood pressure was 220 mm Hg. Computed tomography scan showed a left thalamic hemorrhage with associated edema and hemorrhage extending into the left lateral and third ventricle. She recovered uneventfully and was discharged to inpatient rehabilitation and eventually transitioned home. Three months later in the clinic, she reported that following the stroke, she abruptly stopped smoking without any smoking cessation aid. She reported that she had no craving for cigarettes. She also developed an aversion to drinking alcohol. Discussion: Cessation of smoking following a thalamic intracerebral hemorrhage is not reported earlier. This observation suggests that the thalamus may play a role in nicotine and alcohol addiction. Further studies are needed to elucidate the possible involvement of the thalamic circuits in addiction pathways and as a potential target for modulation.